The Orthopaedic Trauma Service and COVID-19: Practice Considerations to Optimize Outcomes and Limit Exposure. Issue 7 (July 2020) - Stinner, Daniel J.; Lebrun, Christopher; Hsu, Joseph R.; Jahangir, A. Alex; Mir, Hassan R.
Abstract : Abstract: The COVID-19 pandemic has presented challenges to healthcare systems, including the cancellation and then staged resumption of elective procedures. The orthopaedic trauma community has continued to provide care to patients with acute musculoskeletal injuries that cannot be delayed in all scenarios. This article summarizes and provides relevant information (orthopaedic trauma service, outpatient fracture clinic, inpatient surgery) to the practicing orthopaedic traumatologist on maximizing outcomes while limiting exposure during the pandemic. Level of Evidence: Therapeutic Level V. See Instructions for Authors for a complete description of levels of evidence.